Regioselective and efficient enzymatic synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh D.; Paul, Ajay; Mulani, Fayaj A.; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Bioorganic & Medicinal Chemistry Letters, 2018)
Labdane diterpene andrographolide (1) is a major constituent of Andrographis paniculata and known to exhibit wide spectrum of biological activities. In this study, regioselective monoesters of (1) have been synthesized by using Amano lipase AK (Pseudomonas fluorescens) as a biocatalyst. Amano lipase AK was able to execute highly efficient esterification of hydroxyl group attached to C-14 carbon of (1) in presence of acyl donors. Among the various synthesized derivatives including two novel compounds such as andrographolide-14-propionate (3) and andrographolide-14-caproate (5) displayed antimicrobial activity against Staphylococcus aureus with low minimal inhibitory concentration (MIC) 4 mu g/mL and 16 mu g/mL respectively. Furthermore, they have shown low hemolysis activity at their respective MIC and increase in the permeability of the bacterial cell membrane as delineated by FITC uptake and SEM imaging studies. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Andrographolide; Antimicrobial activity; biocatalysis; Hemolysis; Lipase; Natural product